Analysis of Economic Factors Affecting Stock Market - Xie, Linyin (2010)
This dissertation concentrates on analysis of economic factors affecting Chinese stock market through examining relationship between stock market index and economic factors. Six economic variables are examined: industrial production, money supply 1, money supply 2, exchange rate, long-term government bond yield and real estate total value. Stock market comprises fixed interest stocks and equities shares. In this dissertation, stock market is restricted to equity market. The stock price in this dissertation refers to equity price. Shanghai Stock Exchange composite index, Shanghai Stock Exchange A share index and Shanghai Stock Exchange B share index are examined in this dissertation.